Advances in Hydrogel Adhesives for Gastrointestinal Wound Closure and Repair - Xingyu Hu; Mark W. Grinstaff (Gels, 2023)
Millions of individuals undergo gastrointestinal (GI) tract surgeries each year with common postoperative complications including bleeding, perforation, anastomotic leakage, and infection. Today, techniques such as suturing and stapling seal internal wounds, and electrocoagulation stops bleeding. These methods induce secondary damage to the tissue and can be technically difficult to perform depending on the wound site location. To overcome these challenges and to further advance wound closure, hydrogel adhesives are being investigated to specifically target GI tract wounds because of their atraumatic nature, fluid-tight sealing capability, favorable wound healing properties, and facile application. However, challenges remain that limit their use, such as weak underwater adhesive strength, slow gelation, and/or acidic degradation. In this review, we summarize recent advances in hydrogel adhesives to treat various GI tract wounds, with a focus on novel material designs and compositions to combat the environment-specific challenges of GI injury. We conclude with a discussion of potential opportunities from both research and clinical perspectives.